The Method of Solving Literary Problems and the Problem-Based School Essay in Grammar School - Žbogar, Alenka (Slavia Centralis, 2023)
We develop an original method of teaching literature, exemplary for the problem-based teaching of Slovenian in grammar schools, called the method of solving literary problems. New methods and approaches in literature class require different verification and assessment of knowledge. We turn the classic school essay into a problem-based one, and determine the characteristics of the structure, the proportions of the final grade and the taxonomy of the problem-based essay.
Keywords: method of solving literary problems, grammar school, literature at Slovenian classes, problem-based school essay